GENDER REPRESENTATION IN @SONU_PAII PAID PROMOTIONAL VIDEOS: AN EXPERIENTIAL METAFUNCTION ANALYSIS - Adelia Sari Sitompul; Siti Aisah Ginting; Widya Andayani (English Education Department at FKIP Nommensen University, 2026)
Gender has long been recognized as a significant social factor influencing language use, reflecting how people express their identity, power, and social roles via communication. Gender representation is expressed on social media in both linguistic and multimodal formats, including text, emojis, visuals, sound, and gestures. From a linguistic perspective, this gender performance is realized through the experiential and logical metafunctions of language Systemic Functional Linguistics (SFL) developed by Halliday (2014), especially experiential metafunction. The experiential metafunction refers to how language encodes experiences of the world, including actions, perceptions, states, and relationships. It is realized through the transitivity system, which consists of processes (material, mental, relational, verbal, behavioral, existential), participants, and circumstances. This research therefore aims to investigate how experiential metafunctions are realized in the influencer’s paid promotional videos, and how representation of gender of @sonu_paii.